X-Ray diffraction analysis and modeling of the depth profile of lattice strains in AlGaN stacks - Rafaja, D.; Fischer, P.; Barchuk, M.; Motylenko, M.; Roeder, C.; Besendoerfer, S.; Meißner, Elke (Thin Solid Films, 2021)
One of the requirements for the functionality of the AlGaN/GaN high-electron mobility transistors is the presence of a specific residual lattice strain in their active region. This lattice strain can be adjusted by depositing a multilayer stack that consists of individual AlxGa1−xN layers with harmonized [Al]/[Ga] ratio, which produces a controlled depth gradient of the lattice misfit and consequently a controlled gradient of the residual lattice strain. However, the lattice misfit at the interfaces between adjacent layers is partially compensated by misfit dislocations and other microstructure features, e.g., V-shaped interfacial pyramids. In this contribution, a non-destructive method for simultaneous quantitative analysis of remaining lattice strains and density of microstructure defects compensating the lattice misfit is presented and illustrated on the example of AlGaN stacks with different composition profiles, which were deposited using metalorganic chemical vapor phase epitaxy on (111)-oriented Si wafers. This technique is based on the mapping of selected reciprocal lattice points using X-ray diffraction. The lattice strains obtained from the reciprocal space mapping were verified by confocal micro-Raman spectroscopy. The presence of the microstructure defects and the depth gradient of their density were confirmed by transmission electron microscopy. The interplay of the composition profile and the thickness of individual layers on the lattice strain is described by a micromechanical model. From the comparison of the experimental results with the lattice strains, which were predicted for a defect-free multilayer stack, the main strain relaxation mechanisms are concluded, and their impact on the strain relaxation is quantified.
CRIS-Team Scopus Importer:2021-07-23
Keywords: AlGaN multilayer stacks; Lattice strain; Microstructure defects; Raman spectroscopy; Transmission electron microscopy; X-Ray diffraction